Promotion and Development of Wine Tourism In the Republic of Moldova - Burbulea, Rodica; Movileanu, Veronica (Acta Universitatis Danubius. Œconomica, 2022)
Tourism is a way of life in the contemporary world that represents an important force for the development, prosperity and well-being of nations. Over the last two decades, wine tourism has experienced a continuous expansion, with average annual growth rates of between 5 and 10%, thus becoming a sector of major importance for both the world's major powers and developing countries. It is important to note that tourism, as a branch of economic interference, drives and stimulates the production of other economic areas. The research carried out in this paper has shown that the activity of some fields is largely determined by the needs of tourism and tourists, which are very varied and constantly changing. Under these conditions, there is a need to adapt the tourism industry to the increasingly diverse and complex requirements of tourists, causing the state and private economic agents to modernize the technical and material base and infrastructure, while developing new forms of tourism one of them being wine tourism.